Rumbai Bridge Sound Design in Multimedia Music - Kurniawan, Agung; Nofridayati, Nofridayati; Yusnelli, Yusnelli; Awerman, Awerman; Syaputra, Weldi (Institut Seni Indonesia Padangpanjang, 2024)
The work entitled Sound of Rumbai Bridge is a work of electronic music using the concept of Sound Design which is applied to atmospheric objects on the Rumbai Bridge. This work is divided into two parts, namely the sound exploration process, where the artist takes sounds from activities that occur around the Rumbai Bridge, and the sound development process, where the creator develops the sounds that the creator has obtained. The process of creating the work Sound Of Rumbai Bridge includes Sound Design techniques, namely: Splicing, Looping, Panning, Automation Volume, Reverb, and Delay as well as equalizing. The results of the Sound Of Rumbai Bridge work will be in the form of stereo audio and video to support the work of Sound Of Rumbai Bridge.